International and Regional Agreements and the Evolution of Consumer Protection in Cross-Border E-Commerce: Indonesia Within ASEAN - Prabowo, M. Shidqon; Teeraphan, Papontee (APPTHI, 2025)
This study examines the role of international and regional agreements in shaping Indonesia’s consumer protection framework in cross-border e-commerce, with particular reference to the Association of Southeast Asian Nations (ASEAN). It addresses three key issues: the extent to which such agreements influence normative legal development, how far these commitments are implemented domestically, and what gaps persist between legal harmonization and practical enforcement. Using a normative juridical (doctrinal) approach, the study analyzes Indonesian laws alongside regional instruments such as the ASEAN Agreement on E-Commerce, the findings indicate that ASEAN frameworks significantly contribute to regulatory alignment, promoting harmonization, cooperation, and the adoption of international best practices. However, this alignment remains largely formal. Substantial gaps persist in enforcement, particularly in relation to standard-form contracts, jurisdictional uncertainty, institutional limitations, and the underdevelopment of online dispute resolution mechanisms. The study concludes that effective consumer protection requires not only legal convergence but also stronger institutional capacity, clearer private international law rules, and integrated dispute resolution systems. Bridging the gap between normative commitments and practical implementation is essential for ensuring meaningful consumer protection in Indonesia’s evolving digital economy.